The educational reform of 1905: State, indigenous y racialized politics in the Aristocratic Republic - Ccahuana Córdova, Jorge Alberto (2019)
This article seeks to demonstrate that the interest of a sector of Peru’s elite in modernizing public education, and using it as a tool for indigenous modernization, was closely linked with their racial conceptualization of Peruvian society in the early 20th century. This vision is evident in speeches as well as in increases to the education budget, constraints placed on rural education, and the implementation of differentiated teacher-training schools.